Pelatihan Manajemen Emosional terhadap Perilaku Caring Perawat - IGAA Sherlyna Prihandhani; Made Oktaviani Bulan Trisna; Ni Kadek Ayu Trya Septi Getsuyobi (Jurnal Keperawatan Silampari, 2022)
This study aims to determine emotional management training on nurses' caring behavior. This research method is a quantitative study with a quasi-experimental pre-test and post-test design using a control group. The results showed that the statistical tests using Mann Whitney obtained a p-value of 0.009. In conclusion, there is an effect of emotional management training on the caring behavior of nurses at Balimed Denpasar Hospital. Keywords: Emotional Management, Training, Nurse Caring Behavior